Evolution of Blood-Brain Barrier Permeability in Subacute Ischemic Stroke and Associations With Serum Biomarkers and Functional Outcome - Müller, Sarah; Kufner, Anna; Dell'Orco, Andrea; Rackoll, Torsten; Mekle, Ralf; Piper, Sophie K.; Fiebach, Jochen B.; Villringer, Kersten; Flöel, Agnes; Endres, Matthias; Ebinger, Martin; Nave, Alexander H. (Frontiers in Neurology, 2021)
Background and Purpose: In the setting of acute ischemic stroke, increased blood-brain barrier permeability (BBBP) as a sign of injury is believed to be associated with increased risk of poor outcome. Pre-clinical studies show that selected serum biomarkers including C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNFα), matrix metallopeptidases (MMP), and vascular endothelial growth factors (VEGFs) may play a role in BBBP post-stroke. In the subacute phase of stroke, increased BBBP may also be caused by regenerative mechanisms such as vascular remodeling and therefore may improve functional recovery. Our aim was to investigate the evolution of BBBP in ischemic stroke using contrast-enhanced (CE) magnetic resonance imaging (MRI) and to analyze potential associations with blood-derived biomarkers as well as functional recovery in subacute ischemic stroke patients. Methods: This is an exploratory analysis of subacute ischemic stroke patients enrolled in the BAPTISe study nested within the randomized controlled PHYS-STROKE trial (interventions: 4 weeks of aerobic fitness training vs. relaxation). Patients with at least one CE-MRI before (v1) or after (v2) the intervention were eligible for this analysis. The prevalence of increased BBBP was visually assessed on T1-weighted MR-images based on extent of contrast-agent enhancement within the ischemic lesion. The intensity of increased BBBP was assessed semi-quantitatively by normalizing the mean voxel intensity within the region of interest (ROI) to the contralateral hemisphere (“normalized CE-ROI”). Selected serum biomarkers (high-sensitive CRP, IL-6, TNF-α, MMP-9, and VEGF) at v1 (before intervention) were analyzed as continuous and dichotomized variables defined by laboratory cut-off levels. Functional outcome was assessed at 6 months after stroke using the modified Rankin Scale (mRS). Results: Ninety-three patients with a median baseline NIHSS of 9 [IQR 6–12] were included into the analysis. The median time to v1 MRI was 30 days [IQR 18–37], and the median lesion volume on v1 MRI was 4 ml [IQR 1.2–23.4]. Seventy patients (80%) had increased BBBP visible on v1 MRI. After the trial intervention, increased BBBP was still detectable in 52 patients (74%) on v2 MRI. The median time to v2 MRI was 56 days [IQR 46–67]. The presence of increased BBBP on v1 MRI was associated with larger lesion volumes and more severe strokes. Aerobic fitness training did not influence the increase of BBBP evaluated at v2. In linear mixed models, the time from stroke onset to MRI was inversely associated with normalized CE-ROI (coefficient −0.002, Standard Error 0.007, p < 0.01). Selected serum biomarkers were not associated with the presence or evolution of increased BBBP. Multivariable regression analysis did not identify the occurrence or evolution of increased BBBP as an independent predictor of favorable functional outcome post-stroke. Conclusion: In patients with moderate-to-severe subacute stroke, three out of four patients demonstrated increased BBB permeability, which decreased over time. The presence of increased BBBP was associated with larger lesion volumes and more severe strokes. We could not detect an association between selected serum biomarkers of inflammation and an increased BBBP in this cohort. No clear association with favorable functional outcome was observed. Trial registration: NCT01954797.